Design And Evaluation Of Multiparticulate Systems Prepared Using Sieving-Spheronisation And Extrusionspheronisation - Karim, Sabiha (2011)

(untitled)
Pelletised dosage forms can be prepared by different methods which, in general, are time consuming and labor intensive. The current study was carried out to assess the feasibility of preparing spherical pellets by sieving the wet powder mass followed by spheronisation. This method was compared with extrusion-spheronisation process in terms of physical characteristics and in-vitro dissolution profile of the developed formulations. The fast release paracetamol pellets were comprised of, microcrystalline cellulose, lactose, crospovidone and polyvinyl pyrrolidone-K90.